(untitled) (International Conference on Education, Psychology and Humanities, 2026)
This article examines the key issues of developing foreign language teaching methodology in higher education institutions from both theoretical and practical perspectives. The study is based on statistical data from international organizations such as UNESCO, OECD, Eurostat, and EF EPI, which highlight global trends in foreign language competence. The findings indicate that the growth of academic mobility, massification of higher education, and the expansion of multilingual policies significantly increase the demand for effective foreign language teaching methodologies.